ANALISIS KESIAPAN PELAKSANAAN DAN EVALUASI PEMBELAJARAN MASA PANDEMI COVID 19 JENJANG SEKOLAH DASAR DI KOTA RUTENG - Adrianus Jemadis Jemadis; Hendrikus Midun; Arsenia Mensiana; Ardiana Aci Sarni; Arnoldus Beatominu Karim (Unika Santu Paulus Ruteng, 2022)
Online learning is a face-to-face learning transformation during the Covid-19 pandemic. The effectiveness of online learning depends on the readiness of schools, teachers and students. This study aims at describing the readiness for implementation and evaluation of learning during the Covid-19 pandemic at the elementary school level. This study used a quantitative approach. The population of the study was teachers at elementary schools in Langke Rembong sub-district, Manggarai Regency, NTT. The sample selection was carried out purposively by considering the status of private and public schools. The total sample of the study was 43 people from the 10 schools. The research instrument was questionnaires which were given given to respondents via Google Form. The period for distributing the questionnaire was April and May 2021. The data analysis technique was a percentage description. The findings of the analysis revealed that the implementation of online learning and evaluation of student learning outcomes during the Covid-19 pandemic at elementary schools in the Langke Rembong sub-district, Manggarai Regency, NTT were very diverse. There is a strong tendency for teachers to use limited face-to-face learning, there are 54% of teachers who answer very often and often tend to carry out traditional learning. The results of this study have implications for efforts to empower schools, teachers and students to improve the implementation of online learning and some similar research implications in the future.